2018
DOI: 10.1177/1087054718757647
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Aerobic Exercise on Cognitive Flexibility and Task-Related Heart Rate Variability in Children With ADHD and Healthy Controls

Abstract: The findings suggest that exercise elicits similar benefits for cognitive flexibility in children with ADHD and healthy controls, partly due to an increase in arousal induced by parasympathetic withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 55 publications
(91 reference statements)
3
33
2
1
Order By: Relevance
“…The studies have hereby identified exercise-induced improvements in response inhibition, impulsivity, and attention as assessed by the flanker task [72,105], Go/Nogo task [21], and Stroop task [17,102]. In addition, exercise-induced enhancements in task switching [17, 50,] and cognitive flexibility [73] have been shown. Piepmeier et al [102] further demonstrated that some aspects of executive functioning seem to benefit from acute exercise while others do not.…”
Section: Neurocognitive Effects Of Physical Exercise In Adhd Acute Efmentioning
confidence: 94%
“…The studies have hereby identified exercise-induced improvements in response inhibition, impulsivity, and attention as assessed by the flanker task [72,105], Go/Nogo task [21], and Stroop task [17,102]. In addition, exercise-induced enhancements in task switching [17, 50,] and cognitive flexibility [73] have been shown. Piepmeier et al [102] further demonstrated that some aspects of executive functioning seem to benefit from acute exercise while others do not.…”
Section: Neurocognitive Effects Of Physical Exercise In Adhd Acute Efmentioning
confidence: 94%
“…Of note, one recent study indicated that acute MAE resulted in increased LF/HF ratio driven by parasympathetic withdrawal shortly after (i.e., 15-20 min) exercise cessation in children with ADHD. Authors of the study interpreted their findings as a favorable change of sympathovagal balance and prefrontal cortex activity induced by acute aerobic exercise 26 . Given the close relationship between prefrontal brain function and sympathovagal control 22 accompanied by a sympathovagal imbalance in children with ADHD 24 , it is appealing to have a sustained measurement of HRV following acute exercise in this particular group to gain better insight of the mechanisms underlying inhibitory control.…”
mentioning
confidence: 99%
“…It was hypothesized that acute MAE would result in better inhibitory control performance, accompanied by larger N2 and P3 amplitude reflecting the optimization of neuroelectric processes underlying improvements in cognition among a sample of children characterized by lower attentional inhibition capabilities. Further, it was hypothesized that acute MAE would result in increased post-exercise LF/HF ratio 26 relative to baseline and when compared to a physically inactive control intervention, reflecting more favorable ANS modulations during post-exercise recovery. From a public health standpoint, the current investigation provides practical insight into the utility of acute bouts of MAE as a complementary behavioral treatment to manage ADHD symptoms.…”
mentioning
confidence: 99%
“…Future work should investigate in more detail the possibility that the cross-sectional relationships we observed were mediated by other, unobserved factors. Primary candidates include traffic-related air pollution (Sunyer et al, 2015); aerobic exercise (Ludyga et al, 2018); media use (Beyens, Valkenburg, & Piotrowski, 2018) and different parenting styles (Glynn & Baram, 2019). Recording these measures repeatedly, in a longitudinal study, will also give more insight into developmental trajectories.…”
Section: Discussionmentioning
confidence: 99%